Comparison of Transperianal Ultrasound With Colonoscopy and Magnetic Resonance Imaging in Perianal Crohn Disease. Issue 4 (April 2018) - Lee, Eun Hye; Yang, Hye Ran; Kim, Ji Young
ABSTRACT: Objective: Perianal fistulae and/or abscesses are common complications of Crohn disease (CD), especially in children. Magnetic resonance imaging (MRI) and gross examination under anesthesia are accurate diagnostic modalities for evaluating perianal lesions. Both methods, however, are expensive and have some limitations for use in children. This study aims to assess the accuracy of transperianal ultrasound (TPUS) and colonoscopic examination, compared with MRI, in pediatric patients with perianal CD (PACD). Methods: Thirty-eight children and adolescents with PACD who underwent MRI, TPUS, and gross colonoscopic examination under sedation were included. Fistulae were classified according to Parks' and St. James's University Hospital classifications. Abscesses were identified by their presence and location on each modality. Results: Fifty-nine fistulae (26 superficial, 23 intersphincteric, 10 transsphincteric) and 16 abscesses were detected using MRI. Fifty-nine fistulae and 10 abscesses were detected using TPUS. Forty-five fistulae (sensitivity 76.3%, positive predictive value [PPV] 84.2%, and kappa value 0.296] and 9 abscesses (sensitivity 56.3%, PPV 90.0%, and kappa value 0.624) on TPUS corresponded with MRI findings. Forty-six fistulae and fifteen abscesses were detected using colonoscopy. Forty fistulae (sensitivity 67.8%, PPV 89.9%, and kappa value 0.369) and 7 abscesses (sensitivity 43.8%, PPV 48.8%, and kappa value 0.304) on colonoscopy corresponded with MRI findings. With respect to abscess, agreement between TPUS and MRI was superior to that between colonoscopy and MRI (Spearman rho 0.651 vs 0.304, P  = 0.007). Conclusion: TPUS is an appropriate, simple, and real-time method for detecting perianal fistula and/or abscess, in children with PACD. Abstract : Supplemental Digital Content is available in the text